SUMBER BELAJAR DONGENG YANG BERMUATAN KONSERVASI BUDAYA Ã¢â‚¬Å“BANYUMASANÃ¢â‚¬Â - Febriani, Meina; Sugiarto, Eko (Badan Pengembang Konservasi UNNES, 2018)
Local culture is a content that can be used in the preparation of textbook material. Javanese culture (Banyumasan) as having noble values that should be understood by children, especially at the primary education level in Banyumas Regency. This research reveals: the type of Banyumasan fable and its potential as a source of learning as the conservation of Banyumasan culture through education. Research uses a qualitative approach to case study design. This research is believed to provide theoretical benefits about the concept of learning art and literature. The results show that Banyumas has various folklore with Banyumasan values. Tales that contain conservation of Banyumasan culture can potentially be a source of learning (enrichment) for children in the education process.